DEIKSIS BAHASA MELAYU DIALEK SAMBAS DALAM FILM KUALI HANGUS - Rohim Nurlia; Patriantoro Patriantoro; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract.The Kuali Hangus film is one of the regional films of Sambas Regency, West Kalimantan, in the Selakau District. The research problem was how persona deixis, place deixis, time deixis in a dialect of Sambas Malay, and the implementation plans of drama texts in learning Indonesian in high school class XI. The method used in this research was a qualitative descriptive study. The data and the data sources were the Sambas dialect Malay words and phrases enclosed in the film Kuali Hangus. The techniques of data collecting was documentary, meanwhile, the tools of data collecting were the researcher as key instruments. The technique of data validity conversion and the data analysis were obtained through the observation persistence, references adequacy, and lecturers’ guidance based. Based on the research findings, there were three deixes. First, the person deixis, it was divided into three the first, second, and third-person deixis. Then, the place deixis comprised of three, deixis proximal, semi-proximal, and distal places. Finally, time deixis that divided into two, deixis of present and pastime. This research was expected to be used as teaching material in learning         Indonesian curriculum 2013 in the eleventh grade of high school.  Keywords: Deixis, Film, Implementation